IMPLEMENTASI ELECTRONIC HUMAN RESOURCE MANAGEMENT (E-HRM) DALAM MENINGKATKAN EFEKTIVITAS KINERJA SDM PADA UMKM DI ERA INDUSTRY 4.0 - Wahyunah Febi Pratama; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the implementation of Electronic Human Resource Management (E-HRM) in improving the effectiveness of human resource performance in Micro, Small, and Medium Enterprises (MSMEs) in the Industry 4.0 era. The research method used is a qualitative approach with a descriptive method through a literature study. The data used are secondary data obtained from scientific journals, books, and previous studies relevant to the research topic. The results show that the implementation of E-HRM plays an important role in improving the effectiveness of human resource performance, particularly in terms of time efficiency, productivity, work quality, and accuracy in decision- making. However, the implementation of E-HRM in MSMEs still faces several challenges, such as limited resources, low digital literacy, and inadequate technological infrastructure. Therefore, efforts are needed to enhance understanding and support from various parties to optimize the implementation of E-HRM in MSMEs.